The clinical efficacy and safety of ERCP in traumatic pancreatic injuries: a systematic review and meta-analysis - Hulusi Can Karpuzcu; Çağdaş Erdoğan (World Journal of Emergency Surgery)
Abstract Objectives Traumatic pancreatic injuries (TPI) are rare, critical complications increasingly managed by minimally invasive Endoscopic Retrograde Cholangiopancreatography (ERCP). We systematically reviewed and meta-analyzed ERCP’s efficacy and safety for TPI regarding pancreatic duct integrity and clinical outcomes in diverse populations. Methods PubMed, Scopus, Cochrane Library, and Web of Science were searched (2000–2024) for studies reporting on ERCP for TPI. Primary outcomes were pancreatic duct integrity and complications; secondary outcomes included mortality and hospital stay. Pediatric and adult populations were compared via subgroup analysis. Publication bias was assessed. Results Fifteen studies comprising 1,823 patients (54% male, 32% pediatric) were included in the meta-analysis. ERCP demonstrated a pooled clinical success rate of 89% (95% CI: 83–93%) and significantly improved pancreatic duct integrity (OR for pancreatic duct integrity: 9.17, 95% CI: 6.73–12.49). Complication rates ranged from 4 to 17%, with pancreatitis and bleeding being the most common adverse events. Mortality rates were low (3–5%), and ERCP significantly reduced hospital stay by an average of 3.1 days compared to surgical interventions. Pediatric patients had slightly lower success rates (OR: 6.73, 95% CI: 4.01–11.31) compared to adults (OR: 10.87, 95% CI: 7.40–15.98). Conclusions ERCP is an effective and safe modality for managing TPI in both pediatric and adult patients, yielding high success rates in maintaining ductal integrity and reducing complications, although interpretation requires caution due to potential publication bias. Further prospective studies are required to optimize standardized protocols.